Implementasi Market Day melalui Permainan Petualangan Harta Karun untuk Mengembangkan Literasi Keuangan Anak Usia Dini - Zuhriya Lutfi Rohamtina; Sulhatul Habibah; Moh. Vito Miftahul Munif (AJER: Advanced Journal of Education and Religion, 2026)
Early childhood still has difficulty in understanding the concept of financial literacy due to the limited learning media that are interesting and appropriate to their developmental stage. Research on financial literacy at Dharma Wanita Balungtawun Sukodadi Kindergarten found that the average student has not been able to understand financial literacy and has not been able to manage the expenditure of pocket money given by their respective parents. This study aims to (1) describe the implementation of Market Day through the Treasure Adventure game to introduce and develop financial literacy at Dharma Wanita Balungtawun Sukodadi Kindergarten. (2) describe the response of early childhood to market day activities through the treasure adventure game in financial literacy learning at Dharma Wanita Balungtawun Sukodadi Kindergarten. The method used is descriptive qualitative, the techniques used include: observation, interviews, and documentation techniques. The results of the study (1) market day through treasure adventure games can introduce and develop financial literacy in Dharma Wanita Balungtawun Kindergarten by differentiating money, understanding the value of money and making decisions regarding the wise use of money (2) The children's response to this activity was very positive, shown by enthusiasm, increasing social attitudes such as taking turns, and being able to participate in activities well.